2003
DOI: 10.1590/s0034-89102003000200004
|View full text |Cite
|
Sign up to set email alerts
|

Interrupção do acompanhamento clínico ambulatorial de pacientes infectados pelo HIV

Abstract: OBJETIVO: Determinar os fatores associados à interrupção do acompanhamento clínico ambulatorial de pacientes com infecção pelo HIV. MÉTODOS: Foi realizado um estudo do tipo prospectivo não-concorrente (coorte histórica) no município de Belo Horizonte, MG, em um ambulatório público de referência para atendimento de pacientes com infecção pelo HIV/Aids. Foram revisados registros médicos para se avaliar os fatores associados à interrupção do acompanhamento clínico por pacientes soropositivos para o HIV admitidos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
(16 reference statements)
0
5
1
5
Order By: Relevance
“…CD4 counting lower than 200 cells/mm 3 is also an important factor in determining the death occurrence caused by HIV/aids (30) . A 2003 study in Belo Horizonte related that patients who regularly attended consultations showed an average follow-up period of 37.2 months over two years, while our data observed an average period of 42.4 months during the studied period (10) . Considering the average viral load of patients who attended consultations regularly, our data showed that it was lower than the average of patients who did not attend consultations, while CD4 dosage was higher.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…CD4 counting lower than 200 cells/mm 3 is also an important factor in determining the death occurrence caused by HIV/aids (30) . A 2003 study in Belo Horizonte related that patients who regularly attended consultations showed an average follow-up period of 37.2 months over two years, while our data observed an average period of 42.4 months during the studied period (10) . Considering the average viral load of patients who attended consultations regularly, our data showed that it was lower than the average of patients who did not attend consultations, while CD4 dosage was higher.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, despite the increase of cases in females, it seems to be consensual in the various studies that males still dominate individuals affected by HIV/aids. A prospective study in a reference clinic in the city of Belo Horizonte, State of Minas Gerais, also showed the prevalence of HIV/aids in male patients, corresponding to 68% (10) . A retrospective study conducted at a tropical diseases reference hospital in the Northeast region, showed that male individuals correspond to 71.3% versus 28.7% of female patients (11) .…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, they may have been erroneously classified as adherent by this source of information. A previous study carried out at the same services showed a rate of interruption of medical follow-up for more than seven months of 54.3% 30 . In addition, analyses that are primarily based on medical records are subject to methodological limitations such as under-reporting and low reliability, which may potentially impair proper interpretations.…”
Section: Discussionmentioning
confidence: 85%
“…Sendo assim, apesar do aumento de casos no sexo feminino, parece ser consenso nos diversos estudos que o sexo masculino ainda predomina entre os indivíduos afetados pelo HIV/aids. Em um estudo prospectivo em ambulatório de referência em Belo Horizonte para pacientes com HIV/aids, também houve predomínio do sexo masculino, correspondendo a 68% dos estudados (10) . Em estudo retrospectivo realizado em um hospital de referência do nordeste para doenças tropicais, os indivíduos do sexo masculino corresponderam a 71,3% da população de pacientes versus 28,7 do sexo feminino (11) .…”
Section: Discussionunclassified